2007
DOI: 10.3168/jds.s0022-0302(07)71551-5
|View full text |Cite
|
Sign up to set email alerts
|

Incontinentia Lactis: Physiology and Anatomy Conducive to Milk Leakage in Dairy Cows

Abstract: Incontinentia lactis is a possible predisposing factor for an elevated level of intramammary infection. The goal of the present study was to investigate possible causes of incontinentia lactis in dairy cows. Two farms that differed in breed composition, but that had similar average milk yields were studied: herd A, 28 kg/d, 31 Red Holstein cows; and herd B, 26 kg/d, 16 Brown Swiss cows. Herd A was classified into 2 groups: incontinentia lactis (ILA group) and control, whereas herd B was exclusively a control h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 35 publications
4
22
1
Order By: Relevance
“…Furthermore, our study indicated that a high extramammary udder pressure increased the risk of milk leakage. For lactating cows, a similar relationship between intramammary udder pressure and milk leakage has been demonstrated (Rovai et al, 2007). In contrast to Rovai et al (2007), our data, however, also revealed a relationship between milk leakage after dry-off, parity, and udder pressure.…”
Section: Udder Pressure and Milk Leakagesupporting
confidence: 74%
See 2 more Smart Citations
“…Furthermore, our study indicated that a high extramammary udder pressure increased the risk of milk leakage. For lactating cows, a similar relationship between intramammary udder pressure and milk leakage has been demonstrated (Rovai et al, 2007). In contrast to Rovai et al (2007), our data, however, also revealed a relationship between milk leakage after dry-off, parity, and udder pressure.…”
Section: Udder Pressure and Milk Leakagesupporting
confidence: 74%
“…For lactating cows, a similar relationship between intramammary udder pressure and milk leakage has been demonstrated (Rovai et al, 2007). In contrast to Rovai et al (2007), our data, however, also revealed a relationship between milk leakage after dry-off, parity, and udder pressure. A relationship between the decreasing integrity of the teat canal in higher-parity cows and enhanced risks for IMI was already demonstrated in a previous study (Ding-well et al, 2004).…”
Section: Udder Pressure and Milk Leakagesupporting
confidence: 74%
See 1 more Smart Citation
“…More objective methods have been used to determine teat length and teat diameter, such as measuring tapes, callipers and transparent open-ended tubes with graduated scales (Bakken, 1981;McKusick, Berger, Thomas, 1999;Rovai, Kollmann, Bruckmaier, 2007;Tilki, Inal, Colak, Garip, 2005). Teat diameters can also be measured using a cutimeter, by removing the calliper spring or by holding the jaws open manually to neutralise the spring pressure (Hamann, Mein, Nipp, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Practices such as abrupt cessation of milking at drying-off ( 1 ), prolonged milking intervals ( 2 ), and incomplete milking at the beginning of the lactation ( 3 , 4 ), may lead to udder distension, milk leakage, and inflammatory responses ( 5 , 6 ). Under such conditions, the animals may experience increased mechanical sensitivity, perhaps to a level where their welfare is negatively affected ( 7 ).…”
Section: Introductionmentioning
confidence: 99%